Dosimetry and characterization of a 25‐MeV proton beam line for preclinical radiobiology research. Issue 5 (14th April 2019) - Constanzo, Julie; Vanstalle, Marie; Finck, Christian; Brasse, David; Rousseau, Marc
Abstract : Purpose: With the increase in proton therapy centers, there is a growing need to make progress in preclinical proton radiation biology to give accessible data to medical physicists and practicing radiation oncologists. Methods: A cyclotron usually producing radioisotopes with a proton beam at an energy of about 25 MeV after acceleration, was used for radiobiology studies. Depleted silicon surface barrier detectors were used for the beam energy measurement. A complementary metal oxide semiconductor (CMOS) sensor and a plastic scintillator detector were used for fluence measurement, and compared to Geant4 and an in‐house analytical dose modeling developed for this purpose. Also, from the energy measurement of each attenuated beam, the dose‐averaged linear energy transfer (LETd ) was calculated with Geant4. Results: The measured proton beam energy was 24.85 ± 0.14 MeV with an energy straggling of 127 ± 22 keV before scattering and extraction in air. The measured flatness was within ± 2.1% over 9 mm in diameter. A wide range of LETd is achievable: constant between the entrance and the exit of the cancer cell sample ranging from 2.2 to 8 keV/μm, beyond 20 keV/μm, and an average of 2–5 keV/μm in a scattering spread‐out Bragg peak calculated for an example of a 6‐mm‐thick xenograft tumor. Conclusion: The dosimetry and the characterization of a 25‐MeV proton beam line for preclinical radiobiology research was performed by measurements and modeling, demonstrating the feasibility of delivering a proton beam for preclinical in vivo and in vitro studies with LETd of clinical interest.